Didactic and Methodical Complex of Formation Process Providing of Socio-Cultural Values of Future Border Guard Officers - Novikova, Tetiana (Pedagogical Discourse, 2016)
In modern society, the formation of personal values and their structures are complex and controversial, due to qualitatively new changes in the structure of social relations, changing ideological orientation of Ukrainian society, the introduction of market economy. Formation of socio-cultural values of the individual has been one of the most urgent problems in any country. Ukraine is not the exception, where modern conditions of social and economic transformation and modernization of education are particularly important in exosphere formation of future professionals. The policy of building a new democratic society needs to educate young people on the basis of democratic, social and cultural values while studying at a university. Understanding scientific-pedagogical management of the nature and importance of social and cultural values, the use of criteria and indicators for their formation in the educational process is an important precondition for improving socio-cultural values in the formation of future officers of the State Border Guard Service of Ukraine. Cultural values formation of cadets is not only education, but also educational purpose, so tangible results can be achieved while achieving the threefold purpose of employment: education, educational and developmental. This educational goal is oriented on the use of certain features of the phenomenon being studied. The educational goal provides education, communication, culture, values, character traits: teamwork, activity, patriotism. Objective aim is to provide training and development of intellectual skills. In view of this we can conclude that purposeful shaping of social and cultural values provided the best combination of different activities (training, service), understanding their contents, using a complex of effective forms and methods aimed at achievement a positive result. Teaching in higher education involves not only the acquisition and securing the necessary professional knowledge and skills, but also is accompanied by the formation of personal qualities, professional character traits, values, interests and so on. It should be noted that the formation of social and cultural values, due to the general patterns of socialization (development) of an individual, is influenced by the peculiarities of a human psyche and gained experience. In the present article, the author analyzes the problem of didactic and methodical complex that provides the formation of social and cultural values of future borderguard officers. The thesis determines the main components of didactic and methodical complex and discloses in detail their contents. Thus, implementation of the specified didactic and methodical complex will improve the existing system of professional training of future officers, predict possible problem points in the educational process, ensure the efficiency of the process of socialization of students in universities and promote the formation of cultural values in teaching humanities. Key words: didactic and methodical complex, future officers, borderguard, guidance, teaching a foreign language.